(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The aerial parts of Nicandra physaloides plant collected from Kenyatta National Hospital grounds were dried and subjected to acid-base extraction and partitioned to obtain alkaloidal and non-alkaloidal extracts. The non-alkaloidal extract yielded three compounds; withanicandrin, β-sitosterol and stigmasterol after column chromatography. Withanicandrin exhibited antifungal activity against Saccharomyces cerevisiae and Candida albicans but lacked antibacterial activity.